Traffic effects on global warming: A review - Slimi, Khalifa; Chrouda, Amani; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2026)
Global warming, driven by rising greenhouse gas (GHG) emissions, is a critical 21st-century challenge, with road traffic being a major contributor. This review examines the link between road traffic and global warming, focusing on emissions like CO2, NOx and particulate matter (PM) from fossil fuel vehicles, as well as indirect effects such as urban heat islands (UHIs) and secondary pollutants. It highlights a rapid and significant reduction in emissions required to meet sustainable transportation systems, including zero-emission vehicles (ZEVs), improved public transit, and policy measures like stricter emission standards and carbon pricing. Behavioral shifts, such as promoting walking, cycling, and reduced travel, are also essential. The review notes regional disparities, with developing nations facing challenges due to rapid urbanization and limited access to clean technologies. It calls for global collaboration, innovation, and equitable policies to ensure a just transition to sustainable mobility. Mitigating road traffic's impact on global warming requires a coordinated, multistakeholder approach, prioritizing clean energy, sustainable infrastructure, and inclusive policies. This review urges immediate action to transform the transportation sector and address the climate crisis.
Keywords: Global warming; Impacts & challenges; Mitigation; Policy & regulations; Tech innovations; Social & behavioral; Global & regional views